Tables to determine global cardiovascular risk at the first level of care - Agustín Paramio Rodríguez; René Oramas González; Albadio Pérez Assef; Fidel Cathcart Roca; Myder Hernández Navas (Revista Habanera de Ciencias Médicas)
Introduction: Determining overall cardiovascular risk is essential for developing prevention policies at the primary level of care.